The role of respect in interactions with police among substance-using African refugee young people in Melbourne, Australia - Horyniak, D.; Higgs, Peter; Cogger, S.; Dietze, P. (2017)
Â© 2017 Taylor & Francis Group, LLC. Racialized policing and substance use are major issues faced by African young people in Australia. In-depth interviews with 18 refugee young people who use alcohol and/or drugs examined interactions with police. Status respect and human respect played important roles in interactions with police. Participants felt unfairly targeted by police and reported that they were disrespected by police through the use of discriminatory language, failing to differentiate between individuals leading to a sense of loss of self-identity, and stereotyping. Development and implementation of programs focusing on building mutual understanding and respect is needed to improve relations between refugee-background youth and police.